2015
DOI: 10.1111/gfs.12174
|View full text |Cite
|
Sign up to set email alerts
|

Forage yield and chemical composition of canola (Brassica napus L.) as affected by sowing methods

Abstract: The sowing method of spring-type canola (Brassica napus L. var. oleifera) for forage has a major influence on its productivity and agronomic management. A field experiment was conducted in Matamoros, Coahuila, Mexico, during two growing seasons (to determine dry matter (DM), crude protein (CP) and net energy for lactation (NE L ) yields, as well as canola forage chemical composition as a function of six sowing methods. The treatments assessed were broadcast sowing and five different row spacings: 0Á19, 0Á38, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 20 publications
(22 reference statements)
1
8
0
11
Order By: Relevance
“…Dry matter yield reduction in canola as an effect of its growth cycle decrease has also been reported in another study [7]. The aim of this study was to evaluate canola forage potential growth established by different sowing methods during two growth cycles (2008-2009 and 2009-2010) and concluded that a higher DM yield was achieved in the second growth cycle.…”
Section: Dry Matter and Nutrient Yieldssupporting
confidence: 57%
See 4 more Smart Citations
“…Dry matter yield reduction in canola as an effect of its growth cycle decrease has also been reported in another study [7]. The aim of this study was to evaluate canola forage potential growth established by different sowing methods during two growth cycles (2008-2009 and 2009-2010) and concluded that a higher DM yield was achieved in the second growth cycle.…”
Section: Dry Matter and Nutrient Yieldssupporting
confidence: 57%
“…Other experiments performed on canola have reported results differing from those observed in this study. An increase in ambient temperature may result in a decrease of CP and ENL contents and an increase of NDF and ADF concentrations in forage [7,32]. In this sense, it has been suggested that an increase in forage fiber is positively related to an increase in cell wall lignificaton, which is an effect of high temperatures during the growth cycle [33].…”
Section: Forage Chemical Compositionmentioning
confidence: 99%
See 3 more Smart Citations